2018
DOI: 10.1007/s40596-018-0895-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Digitally Informed Curriculum in Psychiatry Education and Clinical Practice

Abstract: Technology is rapidly permeating the lives of our patients and influencing the clinical practice of psychiatry [1]. From electronic health record (EHR) systems to patient-focused smartphone apps, the way healthcare professionals communicate information with other professionals and with patients have been reshaped dramatically in the last decade [2]. This is partly due to increased access to smartphones [3], and partly due to nationwide initiatives to modernize the healthcare system with a goal to increase accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Previous research on web-based programmes designed for use on personal computers or laptops has found that individuals have more satisfactory ratings for e-mental health resources than clinicians do (Gun et al, 2011;Waller and Gilbody, 2009). There may also be a discrepancy between younger, early career mental health clinicians and older, more experienced clinicians in their knowledge and desire to incorporate digital tools into their practice (Kim et al, 2018). Furthermore, clinicians have indicated specific barriers to using online resources, including concerns about privacy and data security (Hendrikoff et al, 2019;Neary and Schueller, 2018;Stawarz et al, 2018;Terry and Gunter, 2018), lack of time to learn and understand how various online tools work, inability to access relevant training and concerns about client feedback (Sinclair et al, 2013).…”
Section: Clinical or Gimmickal: The Use And Effectiveness Of E-mentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on web-based programmes designed for use on personal computers or laptops has found that individuals have more satisfactory ratings for e-mental health resources than clinicians do (Gun et al, 2011;Waller and Gilbody, 2009). There may also be a discrepancy between younger, early career mental health clinicians and older, more experienced clinicians in their knowledge and desire to incorporate digital tools into their practice (Kim et al, 2018). Furthermore, clinicians have indicated specific barriers to using online resources, including concerns about privacy and data security (Hendrikoff et al, 2019;Neary and Schueller, 2018;Stawarz et al, 2018;Terry and Gunter, 2018), lack of time to learn and understand how various online tools work, inability to access relevant training and concerns about client feedback (Sinclair et al, 2013).…”
Section: Clinical or Gimmickal: The Use And Effectiveness Of E-mentalmentioning
confidence: 99%
“…Thus, the clinician's perspective would appear to be vital in the successful uptake and wider dissemination of e-mental health resources (Hollis et al, 2018;Martinez-Martin and Kreitmair, 2018). Furthermore, there is a distinct lack of teaching about how to incorporate digital tools into practice in academic mental health programmes, including for those training to be psychiatrists (Kim et al, 2018;Torous et al, 2018a).…”
Section: Clinical or Gimmickal: The Use And Effectiveness Of E-mentalmentioning
confidence: 99%
“…Through the internet, providers can attend online lectures remotely and earn credits. Psychiatrists have also used technology to share ideas and collaborate virtually through software and connected devices, including teleconferencing, cloud drives, and shared online notebooks [35]. Though this sounds very exciting, it comes with challenges of the convenience of the participants and trainers in the use of technology, availability of high speed internet, making plans to re-engage the drop-outs, etc.…”
Section: Challenges In Digital Learningmentioning
confidence: 99%
“…Clinicians also face systemic barriers, such as issues with insurance reimbursement and concerns regarding patient privacy (Gagnon et al, 2016 ). Clinicians need health systems to support a transition toward a new frontier in mental healthcare, one that effectively meets the growing demand by supporting the incorporation of digital mental health interventions (Gipson et al, 2017 ; Hilty et al, 2020 ; Kim et al, 2018 ; Mohr et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%